Sosialisasi Pengolahan Air Tanah di Kelurahan Borongloe Kecamatan Bontomarannu Kabupaten Gowa - Roslinda Ibrahim; Mary Selintung; Achmad Zubair; Nur An-nisa Putri Mangarengi; Nurjannah Oktorina Abdullah (Faculty of Engineering UNHAS, 2022)
Groundwater is one source of clean water that widely used by people in Indonesia, including in Borongloe Village, Bontomarannu District, Gowa Regency. However, groundwater utilization often experiences problems due to the presence of iron (Fe) and manganese (Mn) in ground water which can cause health problems if consumed continuously. The presence of these two substances in groundwater causes the color of the water to turn yellow-brown after some time in contact with air. In addition, there is often an unpleasant odor and yellow spots on clothes and water storage containers. The purpose of this activity is to increase the knowledge and understanding people of Borongloe Village regarding the requirements for clean water quality and groundwater treatment technology. The method purpose is to achieve the goals that have been set is to carry out socialization of the well water treatment method using a silica sand filter, manganese zeolite and activated carbon. The socialization activity was carried out at the Borongloe village head office, attended by twenty-five participants. The enthusiasm of the participants is very well in participating the socialization, this proved by the sincerity in receiving the material and the desire to ask questions during the activity. The results of the post test showed that 50% - 80% of the participants really understood the socialization material which includes requirements for clean water quality, manufactured and media for clean water filters as well as operation and maintenance of clean water filters.